Pengembangan Sistem Informasi Industri Jasa Menjahit Online Berbasis Web Menggunakan Metode Waterfall - Elsa Oktavia; Yulindon Yulindon; Rahmat Hidayat (UIN Sunan Kalijaga Yogyakarta, 2020)
Information systems are currently increasing very rapidly, but it is unfortunate if the utilization is not yet optimal. Reviewing the data from literature studies and observations that have been made, many people need sewing services. The drastic increase in demand makes competition in the convection industry. Most of the work systems in the convection industry are done manually and are not economical. Product development also lacks creativity. Therefore, this researcher will use IT as marketing and design work, this can make processing time shorter and more optimal. Thus, customers will be facilitated in ordering ready-made clothes or clothes that match the customer's wishes by using a web application that only sends data on the size of the clothes or clothing model that the customer wants. This web-based application system can make it easier for customers to transact with the owner and transactions do not have to meet face to face. In addition, clothing sales and large-scale orders can be neatly organized and financial reports can be well structured and organized clearly. The results of this research will be in the form of research reports and web-based online sewing service information systems using the waterfall method.